REBRAIN GREECE: The Greek Case of Collective Intelligence Ecosystem for Governmental Decision Making - Panopoulos, Dimitris I. (HAPSc Policy Briefs Series, 2020)
REBRAIN GREECE (RBG), a multidisciplinary and inter-ministerial working group, formulated in April 2019, is perhaps the first Greek governmental collective intelligence ecosystem, reaching out to efficiently handle issues of utmost importance, such as brain drain and digital transformation of the existing human resources to the new digital working society. As an ecosystem, it consists of several, thematic, inter-connected working groups, composed of different ministries’ teams of field experts, dealing with concrete but inter-correlated issues, interoperating in a constant way. RBG constitutes a three pillar- interoperability -collective intelligence- ecosystem, encompassed in its functional architecture constant and open source, interoperability synergies between governmental agencies, different field’s experts and ministerial executives, between machine learning schemes and data bases and integrated information systems info exchange modules. It uses the data analytics power of the Labour Market Diagnosis Mechanism (LMDM) and already produced data driven policy proposals. Big data applications of LMDM are interpreting and visualising different types of big data bases through cross-checking raw data and thus formulating approaches towards public policies. Through visualization softwares used for interpreting the data into policy perspectives and proposals, that policy makers examine and elaborate on the most suitable choices and activities for challenge-responsive market digital policies.